PENGARUH DOSIS PUPUK P TERHADAP PERTUMBUHAN BIBIT TANAMAN KARET (Havea brasilliensis. Muell, Arg) YANG BERSIMBIOSISN DENGAN MIKORIZA - Nurmayulis Nurmayulis, Andi Apriany Fatmawaty,Hasan Azhari Harahap; Andi Apriany Fatmawaty; Hasan Azhari Harahap (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
This studyaimed todetermine the influence of P fertilizer on the growth of mycorrizhal rubber seedlings (Havea brasilliensis. Muell, Arg) of PB 260 stum eye clones. The research was carried out in Pagaranri Pargarutan Village, East Angkola Sub District, South Tapanuli District, North Sumatera. It was conducted during January to April 2012 and arranged ina randomized block design with five rates of P fertilizeras treatments i.e 0, 5, 10, 15, 20 g plant-1. The results showed that the effect of P fertilizer was not significant on plant height, stem diameter, number of stems and leaf area but significant on dry weight of roots. Highest root weight was 472.69 mg found inno P fertilizer treatment with the my cor rizhal infection rate was 100%. This infection rate was the same with that in the 5 g P fertilizer rate treatment.